Factor Determinants of Customer Satisfaction with Airline Services Using Big Data Approaches - Yuliani Dwi Lestari; Eko Agus Murjito (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
In the commercial airline’s industry, customer satisfaction is critical. Due to increasingly fierce competition, customer satisfaction can affect airlines’ customer decisions in providing recommendations for prospective customers. For this reason, this study aims to explore the determinant factors that influence customer satisfaction and recommendations for the top 10 airlines listed on the Skytrax list. Using the big data approach, this study collected data from 10.189 customer reviews from 2012 to 2019. Based on the results of statistical analysis using binary logistic regression techniques, it was found that out of 7 factors, only 5 significantly influenced customer recommendations, namely airline rate, seat comfort, cabin staff service, food and beverages, and value for money. In-flight entertainment and ground services were not significant. The findings of this study contribute to strengthening the literature related to customer satisfaction in the airline sector, as well as managerial contributions to be used as a reference for airlines in improving service quality, particularly for long international flights.